Effect of Water Deficit at Vegetative and Reproductive Stages of Hybrid, Open Pollinated Variety and Local Maize (Zea mays L.) - Sah, SK; Zamora, OB (Journal of the Institute of Agriculture and Animal Science, 2005)
A pot experiment was conducted to study the effects of water deficit on vegetative and reproductive stages of Hybrid, Open pollinated (OPV) and Local varieties of maize. Water deficit at vegetative stage significantly reduced plant height, leaf area, shoot dry matter, root dry matter of the upper 25 cm depth, kernel number and grain yield per plant as compared to well watered plant. Water deficit at reproductive stage reduced more leaf area, kernel number and grain yield per plant than water deficit at vegetative stage. Water deficit at reproductive stage also reduced shoot dry matter, kernel size and harvest index. Leaf water potential and relative water content taken at 58 and 60 days after planting were also reduced by water deficit. The Local variety was taller with smaller kernel size and lower harvest index than Open pollinated and Hybrid varieties. There were no significant interactions among the varieties and water deficit treatments. Key words: Leaf water potential, relative water content, vegetative and reproductive stages, harvest index J. Inst. Agric. Anim. Sci. 26:37-42 (2005)